Picturing Russia : explorations in visual culture - Neuberger, Joan; Neuberger, Joan (Yale University Press, 2008)
List of illustrations -- Acknowledgments -- 1: Seeing into being: an introduction / Valerie A Kivelson and Joan Neuberger -- 2: Dirty old books / Simon Franklin -- 3: Visualizing and illustrating early Rus housing / David M Goldfrank -- 4: Crosier of St Stefan of Perm / A V Chernetsov -- 5: Sixteenth-century Muscovite cavalrymen / Donald Ostrowski -- 6: Blessed is the Host of the Heavenly Tsar: an icon from the Dormition Cathedral of the Moscow Kremlin / Daniel Rowland -- 7: Cap of Monomakh / Nancy Shields Kollmann -- 8: Church of the Intercession on the Moat / St Basil's Cathedral / Michael S Flier -- 9: Mapping serfdom: peasant dwellings on seventeenth-century litigation maps / Valerie A Kivelson -- 10: From tsar to emperor: portraits of Aleksei and Peter I / Lindsey Hughes -- 11: Russian Round Table: Aleksei Zubov's depiction of the marriage of his Royal Highness, Peter the First, autocrat of all the Russias / Ernest A Zitser -- 12: Icon of female authority: the St Catherine image of 1721 / Gary Marker -- 13: Conspicuous consumption at the Court of Catherine the Great: Count Zakhar Chernyshev's snuffbox / Douglas Smith -- 14: Moving pictures: the optics of serfdom on the Russian estate / Thomas Newlin -- 15: Neither nobles nor peasants: plain painting and the emergence of the merchant estate / David L Ransel -- 16: Circles on a Square: the heart of St Petersburg culture in the early nineteenth century / Richard Stites -- 17: Alexander Ivanov's appearance of Christ to the people / Laura Engelstein -- 18: Lubki of emancipation / Richard Wortman -- 19: Folk art and social ritual / Alison Hilton -- 20: Personal and imperial: Fyodor Vasiliev's in the Crimean Mountains / Christopher Ely -- 21: Shop signs, monuments, souvenirs: views of the empire in everyday life / Willard Sunderland -- 22: Storming of Kars / Stephen M Norris -- 23: A O Karelin and provincial Bourgeois photography / Catherine Evtuhov -- 24: European fashion in Russia / Christine Ruane -- 25: Savior on the Waters church war memorial in St Petersburg / Nadieszda Kizenko -- 26: Workers in suits: performing the self / Mark D Steinberg -- 27: Visualizing masculinity: the male sex that was not one in Fin-de-Siecle Russia / Louise McReynolds -- 28: Pictographs of power: the 500-ruble note of 1912 / James Cracraft -- 29: Visualizing 1917 / William G Rosenberg -- 30: Looking at Tatlin's stove / Christina Kiaer -- 31: Soviet images of Jehovah in the 1920s / Robert Weinberg -- 32: National types / Francine Hirsch -- 33: Envisioning empire: veils and visual revolution in Soviet Central Asia / Douglas Northrop -- 34: Visual economy of forced labor: Alexander Rodchenko and the White Sea-Baltic Canal / Erika Wolf -- 35: Cinematic pastoral of the 1930s / Emma Widdis -- 36: Portrait of Lenin: carpets and national culture in Soviet Turkmenistan / Adrienne Edgar -- 37: Moscow metro / Mike O'Mahony -- 38: Soviet spectacle: the All-Union Agricultural Exhibition / Evgeny Dobrenko -- 39: Motherland calling? national symbols and the mobilization for war / Karen Petrone -- 40: Visual dialectics: murderous laughter in Eisenstein's Ivan the Terrible / Joan Neuberger -- 41: Soviet Jewish photographers confront World War II and the Holocaust / David Shneer -- 42: Morning of Our Motherland: Fyodor Shurpin's portrait of Stalin / Mark Bassin -- 43: Pioneer Palace in the Lenin Hills / Susan E Reid -- 44: Mikhail Romm's Ordinary Fascism / Josephine Woll -- 45: Solaris and the white, white screen / Lilya Kaganovsky -- 46: After Malevich-variations on the return to the Black Square / Jane A Sharp -- 47: Imagining Soviet rock: Akvarium's Triangle / Polly McMichael -- 48: Keeping the ancient piety: Old Believers and contemporary society / Roy R Robson and Elena B Smilianskaia -- 49: Viktor Vasnetsov's bogatyrs: mythic heroes and Sacrosanct borders go to market / Helena Goscilo -- 50: Landscape and vision at the White Sea-Baltic Canal / Michael Kunichika -- Chronology of Russian history -- Selected bibliography -- List of contributors -- Illustration credits -- Index